Confronting Vegard's rule in Ge1−xSnx epilayers: from fundamentals to the effect of defects. (21st July 2022) - Magalhães, S; Dias, M; Nunes, B; Oliveira, F; Cerqueira, M F; Alves, E
Abstract: Comprehensive and systematic study challenging the application of Vegard's rule to germanium tin solid solutions grown on germanium buffer layers and 100 silicon substrates is presented. The binary's lattice parameters, composition and respective uncertainties are determined through x-ray diffraction via reciprocal space mapping technique employing newly developed software. The tin content is confirmed by Rutherford backscattering spectrometry and energy dispersive x-ray spectroscopy. The statistical agreement between the tin contents derived by the different structural characterization techniques suggests the binary to follow generically the Vegard's rule in the range of low Sn molar fractions (<5%). Phase separation, Sn segregation, point defects, post-growing oxygen impurities, and deteriorated surface morphology are found to be relevant within the ∼200 nm germanium tin films. Although, complex mechanisms triggering composition/strain heterogeneities are found in the analysed Ge1− x Sn x compounds, the deviation from the perfect crystals is suggested to be not enough to distort the in- and out-of-plane lattice parameters away from its empirical linear combination.